‘Aisyiyah dan Pembinaan Pemberdayaan Perempuan sebagai Upaya Mencapai Kesetaraan Gander (Forum Ilmu Sosial, 2017)
Gander's equality is one form of justice that must not only be a discourse but also an idea for a great cause for women's empowerment. The narrowness of the views that sometimes marginalize the routine of women who live a woman's life is only destined to have a future that is nothing more than taking care of Kitchen, Well, Mattress. But in the midst of this anger in 1917 spelled as the starting point of enforcement of Gander equality, one of which brought the mission of the intelligence of women. This year was born a movement of women named 'Aisyiyah. 'Aisyiyah is the first Autonomous Organization owned by Muhammadiyah and the first Women Organization that stood in Indonesia.'Aisyiyah contains a group of Muhammadiyah mothers who are mostly Wives of the Muhammadiyah activists. This is where the ideal of women's empowerment for Gander's equality begins, long before Indonesia's independence and long before the existence of the women's National Commission, Muhammadiyah has established the first women's movement to guard the enforcement of gender equality and the upholding of women's rights in Indonesia.